2020
DOI: 10.1016/j.jairtraman.2020.101917
|View full text |Cite
|
Sign up to set email alerts
|

Strategic design of precautionary measures for airport passengers in times of global health crisis Covid 19: Parametric modelling and processing algorithms

Abstract: Presently, the negative results of a pandemic loom in a threatening manner on an international scale. Facilities such as airports have contributed significantly to the global spread of the COVID-19 virus. Therefore, in order to address this challenge, studies on sanitary risk management and the proper application of countermeasures should be carried out. To measure the consequences over passenger flow, simulation modelling has been set up at Casablanca Mohammed V International Airport. Several scenarios using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Preventing the spread of infectious diseases not only helps the aviation industry, but it also protects people's health ( Tanriverdi et al, 2020 ). Recently, studies have been conducted on the response methods and strategies adopted by airports and airlines to protect health in the post-COVID-19 era from the aspect of the liability of airlines for passenger safety ( Naboush and Alnimer, 2020 ), aircraft cabin turnaround procedures ( Schultz et al, 2020 ), point-to-point long-haul flight business models ( Bauer et al, 2020 ), seat assignments that follow social distancing ( Salari et al, 2020 ), and passenger flow management in airports ( Dabachine et al, 2020 ; Tuchen et al, 2020 ). Throughout the COVID-19 pandemic, passenger processing strategies of airlines and airports changed from “the fastest” approach to “the safest” approach ( Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preventing the spread of infectious diseases not only helps the aviation industry, but it also protects people's health ( Tanriverdi et al, 2020 ). Recently, studies have been conducted on the response methods and strategies adopted by airports and airlines to protect health in the post-COVID-19 era from the aspect of the liability of airlines for passenger safety ( Naboush and Alnimer, 2020 ), aircraft cabin turnaround procedures ( Schultz et al, 2020 ), point-to-point long-haul flight business models ( Bauer et al, 2020 ), seat assignments that follow social distancing ( Salari et al, 2020 ), and passenger flow management in airports ( Dabachine et al, 2020 ; Tuchen et al, 2020 ). Throughout the COVID-19 pandemic, passenger processing strategies of airlines and airports changed from “the fastest” approach to “the safest” approach ( Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other articles analyze the pandemic's socio-economic impacts in the kingdom (45,59). Further papers address some specific impacts of the pandemic, such as on education (60,61), transport (62), quality of life and wellbeing (63)(64)(65), and environmental pollution (66)(67)(68). Ouhsine et al (69) analyze the impacts of the pandemic on solid waste generation at Moroccan households.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the COVID-19 pandemic causes drastic changes to the passenger experience at airports, especially for operations which affect the safety and passenger waiting times and also reduced shopping experiences. Therefore, this leads to a conflict for airport managers, trading between safety and user experience: In the presence of the virus, social distancing is agreed to be one of the main successful measures, yet, affecting the capacity and throughput of an airport significantly ( Dabachine et al, 2020 ).…”
Section: Impact On Passenger-centric Flight Experiencementioning
confidence: 99%
“…With the Wroclaw Airport, Poland, as an example, the impact of social distance on the performance of security control lanes was investigated ( Kierzkowski and Kisiel, 2020 ); the authors found that different configurations of the security control lanes (Queue-based or Dedicated Stand-based) depend on whether the stakeholder has space to expand the system. With the Casablanca Mohammed V International Airport as an example, it was shown that it is possible to calculate the number of passengers to be processed in accordance with the available check-in counters, while considering sanitary measures ( Dabachine et al, 2020 ). A few recent studies focused on equipment design of new equipment for the purpose of disinfection at airports, for instance, a walk-through-gate with different sensors ( Hossain et al, 2020 ) and a tunnel system similar to the X-ray machines ( Murthy, 2020 ).…”
Section: Impact On Passenger-centric Flight Experiencementioning
confidence: 99%